PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA CIASIHAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Kusumaningrum, Ria; Fauziah, Ratu Dinny; Damayanti, Erlita (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2023)
Implementation of the sharia financial should be directed not only focused on banking activities. Sharia financial system is intended to provide benefits to the economy as a whole, including the management of family finances. Any religion in line with this concept is primarily Islamic as a mercy to the universe. This community service program aimsto socialize sharia economy in family financial management, by taking lessons from family in Ciasihan Village. The result shows the spirit to immediately implement the sharia family financial planning.